Deals the economic structure of business transactions - Klausner, Michael; Subramanian, Guhan (Harvard University Press, 2024)
Drawing on real-life cases from a wide range of industries, two acclaimed experts offer a sophisticated but accessible guide to business deals, designed to maximize value for your side.Business transactions take widely varying forms-from multibillion-dollar corporate mergers to patent licenses to the signing of an all-star quarterback. Yet every deal shares the same goal, or at least should: to maximize the joint value created and to distribute that value among the parties. Building on decades of experience teaching and advising on business deals, Michael Klausner and Guhan Subramanian show how to accomplish this goal through rigorous attention to designing incentives, conveying information, and specifying parties' rights and obligations.Deals captures the range of real-life transactional complexities with case studies covering Microsoft's acquisition of LinkedIn, Scarlett Johansson's contract dispute with Disney over the release of Black Widow, litigation surrounding LVMH's pandemic-disrupted acquisition of Tiffany, the feud between George Norcross and Lewis Katz over ownership of the Philadelphia Inquirer, NBC/Viacom's negotiation with Paramount over the final three seasons of Frasier, and many more. In clear, concise terms, Klausner and Subramanian establish the basic framework of negotiation and the economic concepts that must be addressed in order to maximize value. They show how to tackle challenges, such as information asymmetry between buyer and seller, moral hazard, and opportunistic behavior. And the authors lay out responses to common risks associated with long-term contracts, emphasizing that a deal's exit rights should be carefully considered at the start of transaction design.Unique in its practical application of economic theory to actual dealmaking, this book will be an indispensable resource for students and for professionals across the business and legal world.